Determinants of Bank Capital in Indonesian Islamic Banks - Agus Widarjono; Munrokhim Misanam (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Bank capital is the linchpin for Islamic banks to steer clear insolvency risk. However, studies on Islamic bank capital in Indonesia remain scarce, with existing studies failing to distinguish between Islamic commercial banks and Islamic business units. Our research analyzes the determinants of Islamic bank capital using the latest data and splits them into Islamic commercial banks and Islamic business units. We used quarterly data from 31 Islamic banks from 2014 to 2020. The estimation method used in this study was panel data regression with unbalanced panel data. The results reveal that bank capital is positively affected by bank size, bank margin, and financing. Conversely, competition, inefficiency, and non-performing financing worsen Islamic bank capital. In addition, bank size and margin have a more pronounced impact on Islamic commercial banks than on Islamic business units. However, inefficiency and non-performing financing have a stronger impact on bank capital for Islamic business units than for Islamic commercial banks. These findings have several important implications, suggesting that Islamic bank capital can be boosted through increased margins and efficiency, while reducing impaired financing is crucial for capital accumulation.